Learning on the blog collected posts for educators and parents - Richardson, Will (Thousand Oaks, California Corwin Press, 2011)
"Best-selling author Will Richardson's Learning on the Blog is a compilation of posts by the author on his acclaimed education blog weblogg-ed.com. Each blog specifically relates to trends and goals of the kinds of educational reform that can be accomplished through new technologies. The author reflects on the developments in how technology is used in the classroom, highlighting what we've accomplished and how far we have to go. Each selection includes actions steps for educators on how to address critical issues and provides tips and strategies to effectively integrate technology in the classroom"--Provided by publisher.
Part I: Teachers as Master Learners -- Part II: Learning is Anytime, Anywhere, Anyone -- Part III: The Learner as Network -- Part IV: Learning and Leadership -- Part V: Parent as Partner -- Part VI: The Bigger Shifts: Deal with it.
Includes index.
Keywords: Internet in education; Teaching -- Aids and devices; Blogs; Educational technology; Educational change